The Production Pattern of Rubber Farming and Farmer Behavior in Dealing with Price Fluctuations in Jambi Province, Indonesia - Armen Mara; Fendria Sativa (Universitas Panji Sakti, 2022)
This study aims to determine (1) the magnitude of the fluctuation in rubber prices (2) the pattern of production of rubber and the behavior of farmers in dealing with price fluctuations and (3) the elasticity of the supply of rubber in Jambi Province. This study uses a survey method with the scope of the study area being Jambi Province by selecting two villages purposively, namely Muhajirin Village in Muaro Jambi Regency and Tanah Grow Village in Bungo Regency. Supply elasticity will be analyzed using secondary data and parametric statistical tests. The results showed that the fluctuation in the price of rubber in Jambi Province was quite large, namely Rp. 4,200 per kg in January 2002, then increased to Rp. 43,200 in February 2011, and decreased again to Rp. 6,000 per kg in June 2020. The pattern of rubber production in Muhajirin Village looks irrational where when the price goes down the farmers actually increase their production, that is, in order to meet their daily needs that cannot be reduced. This means that production can still be increased by increasing tapping frequency. The pattern of rubber production in Tanah Tumbuh Village looks rational, where when the price of rubber goes down the farmers do not tap rubber. To meet the needs of farmers, they switch jobs to other fields, such as laboring on plantations, construction workers, or panning for gold. Rubber’s supply elasticity in responding to rubber price changes in Jambi Province is small from one (<1) but the change is significant.